PERHITUNGAN PROFIT TESTING MELALUI PENDEKATAN STOKASTIK PADA ASURANSI UNIT LINK - DIANITA, ULFA; WIDANA, I NYOMAN; JAYANEGARA, KETUT (E-Jurnal Matematika, 2022)
Unit-linked is one of the Insurance Products Associated with Investments. The person who purchase must pay a premium and will get investment return and a death benefits in the event of death during the policy term. So that it is important for companies to calculate cash flow which is in unit link is called profit testing. The purpose of this study is to calculate the profit testing of unit-linked insurance companies through a stochastic approach by considering the calculation of policy value. The calculation of profit testing in this study was carried out through a stochastic approach to the lognormal model. The results of this study are the calculation of profit testing on a policy issued to a life aged 25, 35, 45, and 55 produce a profitable Net Present Value. However, the profits decrease with increasing age of the insured. The results of the calculation also show that the reserve value is  can handle higher risk than quantile reserve.